Pengaruh Beban Kerja dan Ketidakjelasan Peran Terhadap Kinerja Pemeriksa Dengan Stres Kerja Sebagai Variable Mediasi Pada Badan Pemeriksa Keuangan Perwakilan Provinsi Sumatera Barat - Velia Meidilisa; Hendra Lukito (Jurnal Manajemen Stratejik dan Simulasi Bisnis, 2020)
The purpose of this research is to determine workload and role ambiguity effect on job performance with job stress as a mediating variable. This research was conducted at Badan Pemeriksa Keuangan Perwakilan Provinsi Sumatera Barat. The number of samples taken by 54 auditors. The analytical method used was Structural Equation Modelling (SEM) with SmartPLS 3.0 software. The results showed 1) there is a negative and significant effect between workload and job performance, 2) there is a negative and significant effect between role ambiguity an job performance, 3) there is a positive and significant effect between workload and job stress, 4) there is no significant effect between role ambiguity and job stress, 5) there is a positive and significant effect between job stress and job performance, 6) job stress mediate the relationship between workload and job performance, 7) job stress did not mediate the relationship between role ambiguity and job performance.